Comparison of T790M Acquisition After Treatment With First- and Second-Generation Tyrosine-Kinase Inhibitors: A Systematic Review and Network Meta-Analysis - Hsieh, Po-Chun; Wu, Yao-Kuang; Huang, Chun-Yao; Yang, Mei-Chen; Kuo, Chan-Yen; Tzeng, I-Shiang; Lan, Chou-Chin (Frontiers in Oncology, 2022)
Background: Lung adenocarcinoma is a common disease with a high mortality rate. Epidermal growth factor receptor (EGFR) mutations are found in adenocarcinomas, and oral EGFR-tyrosine kinase inhibitors (EGFR-TKIs) show good responses. EGFR-TKI therapy eventually results in resistance, with the most common being T790M. T790M is also a biomarker for predicting resistance to first- and second-generation EGFR-TKIs and is sensitive to osimertinib. The prognosis was better for patients with acquired T790M who were treated with osimertinib than for those treated with chemotherapy. Therefore, T790M mutation is important for deciding further treatment and prognosis. Previous studies based on small sample sizes have reported very different T790 mutation rates. We conducted a meta-analysis to evaluate the T790M mutation rate after EGFR-TKI treatment. Methods: We systematic reviewed the electronic databases to evaluate the T790M mutation rate after treatment with first-generation (gefitinib, erlotinib, and icotinib) and second-generation (afatinib and dacomitinib) EGFR-TKIs. Random-effects network meta-analysis and single-arm meta-analysis were conducted to estimate the T790M mutation rate of the target EGFR-TKIs. Results: A total of 518 studies were identified, of which 29 were included. Compared with afatinib, a higher odds ratio (OR) of the T790M mutation rate was observed after erlotinib [OR = 1.48; 95% confidence interval (CI):1.09–2.00] and gefitinib (OR = 1.45; 95% CI: 1.11–1.90) treatments. An even OR of the T790M mutation rate was noted after icotinib treatment (OR = 0.91, 95% CI: 0.46–1.79) compared with that after afatinib. The T790M mutation rate was significantly lower with afatinib (33%) than that with geﬁtinib (49%) and erlotinib treatments (47%) (p < 0.001). The acquired T790M mutation rate in all participants was lower in Asians (30%) than that in Caucasians (42%). Conclusions: Erlotinib and gefitinib had a higher OR for the T790M mutation than afatinib. The T790M mutation rate was significantly lower in afatinib than in gefitinib and erlotinib. T790M is of great significance because osimertinib shows a good prognosis in patients with T790M mutation.